Efeitos da realidade virtual no tempo de reação motora de crianças com Sindrome de Down: ensaio clínico controlado randomizado - Araújo, Gleicyara Ramã Almeida (Brasil, 2022)
The present study aims to evaluate the effect of motor reaction using virtual reality (VR) in children with Down Syndrome (DS). The study is a randomized controlled clinical trial, carried out at Associação Pestalozzi de Coari, located at Rua Padre Rafael, 1138 – Bairro Duque de Caxias. Zip code: 69460-000, Coari-AM. Six DS children aged 8 to 17 years were included, divided into two groups: control group (CG) and experimental group (EG), which were randomly divided by the online platform www.randomizer.org.br. In both groups, the evaluation was performed using a Treaction application. The experimental group was submitted to a virtual reality training protocol through the Xbox 360º video game. Each session lasted 30 minutes, twice a week, in a total of 10 sessions, the training took place over a period of 2 months (July and August) in the year 2022. The control group received no intervention. Data were analyzed using the Jamovi Training Software for Windows, version 2.2. Through the obtained data, it was verified that there were no significant gains in the motor reaction time when comparing the experimental and control groups. Conclusion: The results in the evaluation with the Treaction application, in children with DS, were not relevant, this fact may have occurred due to the small sample size and/or a good initial motor reaction time of the study participants.